PERAN ADVOKAT DALAM PEMBANGUNAN HUKUM INDONESIA - Mochamad Mansur (Universitas Widya Gama Malang, 2019)
In everyday there are few terms that used to interpret this law profession. Some are termed the lawyers and also use the phrase of legal advisor, lawyer or advocate in Malaysia known as Peguam. The advocates, lawyer and legal advisor terms in english languange also can be called as trial lawyer or specifically in America known as attorney at law as well as in the United Kingdom known as barrister, and the role given by the lawyer that using the legal advisor terms in America known as counselor at law or also solicitor in United Kingdom. In constitution number 18 of 2003 about advocate, the word advocate is used in chapter I about General Conditions explained, Advocate is a person who work as legal professionals, both inside and outside of the court who fulfills the requirements under the provisions of this law. In practice the law profession is not only undertaken by the advocate during examination process at the level of investigation and examination in court (litigation process), however the role of advocate is also seen outside the court. The need for advocate legal services outside the court process is currently increasing, in line with growing needs of the community law, especially in existence that is increasingly open in association between nations. Through consulting services, negotiation and in making contracts for community empowerment and national law reform, especially in the economics and trade, including settlement of disputes outside of the court. Advocates as one element of the justice system is one of the pillars in upholding the rule of law and the human right. Advocates are a noble profession that is closely related to humanity. Increasing capital flows and foreign investment, especially among business people in ASEAN member countries (inter-ASEAN trade and investment), logically it will be followed by an increase in the need of lawyers or legal advisor services. This profession is important in providing direction and legal advices, including the assistance needed by business people properly and protected in Indonesia. Vice versa, when Indonesian business people decided to develop the investment and production activites, for example to Thailand or other ASEAN countries. Indonesian business people will need the services of lawyers or legal advisor who understand the provisions of Thailand laws. The challenges of the advocates basically lies mostly on advocates and the professional advocate commuity to how far the advocates can respond to the problems of the community in his environment. Another challenge is the political climate factor wich is not conducive to developing the role of advocates, for this reason, there is a need for a socialization of the function of the existence of an advocate role both for officials and the general public. These challenges will be increasingly complex when professional skill and the enthusiasm for learning from the lawyers do not grow in accordance with the demands of the global era, including the mastery of foreign languages as a key to opening communication with foreign relation. For this reason, the relationship network with IBA (International BAR Association), ABA (American BAR Association), Lawyer Commitee For Human Rights and the like needs in the era of globization.